First results from HerMES on the evolution of the submillimetre luminosity function - Eales, S.; Raymond, G.; Roseboom, I.; Altieri, B.; Amblard, A.; Arumugam, V.; Auld, R.; Aussel, H.; Babbedge, T.; Blain, A.; Bock, J.; Boselli, A.; et al. (EDP Sciences, 2010)
We have carried out two extremely deep surveys with SPIRE, one of the two cameras on Herschel, at 250 µm, close to the peak of the far-infrared background. We have used the results to investigate the evolution of the rest-frame 250-µm luminosity function out to z = 2. We find evidence for strong evolution out to z $\simeq$ 1 but evidence for at most weak evolution beyond this redshift. Our results suggest that a significant part of the stars and metals in the universe today were formed at z 1.4 in spiral galaxies. © 2010 ESO.